2018
DOI: 10.48550/arxiv.1812.01686
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Continuous Data Assimilation with a Moving Cluster of Data Points for a Reaction Diffusion Equation: A Computational Study

Abstract: Data assimilation is a technique for increasing the accuracy of simulations of solutions to partial differential equations by incorporating observable data into the solution as time evolves. Recently, a promising new algorithm for data assimilation based on feedback-control at the PDE level has been proposed in the pioneering work of Azouani, Olson, and Titi (2014). The standard version of this algorithm is based on measurement from data points that are fixed in space. In this work, we consider the scenario in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Conversely, when an algorithm works in practice, it suggests there might be some analysis to support it. Computational work has demonstrated that nudging over the entire computational domain works much better than required in the rigorous estimates [2,56,28,40,47,48] In our pseudospectral implementation, we have h = 2π/N, so strictly speaking Theorem 2.1 would require N ∼ G exp( √ N /2), which is far from obtainable. Yet our computational results are promising.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, when an algorithm works in practice, it suggests there might be some analysis to support it. Computational work has demonstrated that nudging over the entire computational domain works much better than required in the rigorous estimates [2,56,28,40,47,48] In our pseudospectral implementation, we have h = 2π/N, so strictly speaking Theorem 2.1 would require N ∼ G exp( √ N /2), which is far from obtainable. Yet our computational results are promising.…”
Section: Discussionmentioning
confidence: 99%